Identifikasi Potensi Wisata Sendang Duwur Sebagai Desa Wisata Di Kabupaten Lamongan - Wahyuni, Eka Putri; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2018)
Lamongan regency is a region with many cultural heritage and is also a path of spreading Islam by Walisongo and Sunan in East Java, this makes Lamongan regency famous for its religious tourism, but besides that there is one new alternative tourist destination that is Tourism Village Sendang Duwur. This tourist village has various types of tourism potentials that have not been explored optimally, so it still needs to explore the potential so that it can create new tourism products that are relevant to their potential.                   This study aims to explore the tourism potential in Sendang Duwur Tourism Village , as well as create new tourism products relevant to the available tourism potential. The types of data used qualitative data and quantitative data, with data collection conducted by observation, documentation, literature study and in-depth interviews. Data analysis used is data analysis of flow model consisting of three stages (data reduction, data display, and data verification) by using concept of tourism potency and tourism compone nt concept . The results of this study indicate that in general the Village Tour Sendang Duwur has three types of tourism potential namely the potential of natural tourism, cultural tourism potential, and the potential of man-made tourism, where this potential has not been explored to the fullest. So from the results of potential excavations are created new products relevant to the potential that is owned and certainly can support tourism activities in the Village Tour Sendang Duwur.The creation of new products is expected to increase the variety of attractions contained in the Village Sendang Duwur and of course can be used as a consideration for further development of tourism potential.   Keywords : tourism potential, tourist village, sendang duwur.